1998
DOI: 10.1002/(sici)1096-8652(199801)57:1<51::aid-ajh9>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma: A patient with unusual features including intracranial and meningeal involvement, testicular involvement, organomegaly, and plasma cell leukemia

Abstract: A 27-year-old Chinese male presented with multiple myeloma. Over his 18-month course he manifested a number of unusual features of his disease including his young age, marked organomegaly, a testicular plasmacytoma, multiple intracranial extraskeletal plasmacytomas and meningeal involvement, and peripheral blood plasmacytosis. The case is described and recent literature on these rare manifestations is reviewed. Am. J. Hematol. 57:51-56, 1998.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Extramedullary involvement has been described from 4-11% of multiple myeloma, mostly in the patients experienced a more aggressive disease with a terminal leukemic phase [3]. However, most of published experienced are single case reports about few cases of secondary PCL complicated by cutaneous involvement or with different unusual features, such as intracranial and meningeal involvement, and testicular plasmacytoma [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Extramedullary involvement has been described from 4-11% of multiple myeloma, mostly in the patients experienced a more aggressive disease with a terminal leukemic phase [3]. However, most of published experienced are single case reports about few cases of secondary PCL complicated by cutaneous involvement or with different unusual features, such as intracranial and meningeal involvement, and testicular plasmacytoma [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…The liver and spleen are commonly involved (Colovic et al , 2008). Other extramedullary sites of disease involvement include lymph nodes, skin, central nervous system (CNS), testis, heart and pleura (Colovic et al , 2008; Turhal et al , 1998; Iseki et al , 1987; Klug et al , 1992). Clinical and biological characteristics from six large series of pPCL patients are detailed in Tables I and II.…”
Section: Plasma Cell Leukaemiamentioning
confidence: 99%
“…Intracranial plasmacytoma is also rare, with most cases involving the meninges (meningeal myelomatosis) or the skull rather than the brain parenchyma [8][9][10][11][12]. Of those few cases with cerebral involvement, most had dural attachment and fewer than 10 cases have been reported with isolated intraparenchymal disease [13][14][15][16]. Treatment of intracranial plasmacytoma in the absence of myelomatosis has anecdotally been successful with the use of surgery and radiation, although most cases report follow-up of less than 2 years [8].…”
Section: Discussionmentioning
confidence: 99%
“…There has been little speculation as to the mechanisms of disease localization among these unique patients who present with multiple soft-tissue plasmacytomas [15,17]. Warner and Krueger suggested that hematogenous spread of multiple myeloma may occur via circulating lymphocytes that carry the same idiotypic determinant of the M-protein [18].…”
Section: Discussionmentioning
confidence: 99%